P2X4 and lysosome fusion. (August 2019) - Murrell-Lagnado, Ruth D; Frick, Manfred
Highlights: Activation of lysosomal P2X4 receptors is regulated by luminal pH. In the presence of luminal ATP, alkalinization of luminal pH activates P2X4 in lysosomes and related organelles (LROs). Lysosomal Ca 2+ release via P2X4 promotes lysosome membrane fusion and is dependent upon calmodulin. In LROs P2X4-dependent expansion of the exocytic fusion pore facilitates secretion of contents. Abstract : Similar to other members of the P2X receptor family, the P2X4 receptor at the plasma membrane forms a highly Ca 2+ permeable, non-selective cation channel that is activated by extracellular ATP. Yet, P2X4 differs from the other subtypes, as it is predominantly localized on late endosomal, lysosomal and/or lysosome-related organelles. It is targeted there by virtue of tyrosine-based and di-leucine like trafficking motifs contained within its C-terminal and N-terminal regions respectively. The physiological role of the stable intracellular expression of P2X4 in acidic compartments has been a long-standing puzzle. Recent evidence, however, points to a dual role in the regulation of ion fluxes across lysosomal membranes to control lysosome membrane fusion and in the re-sensitization of receptors exposed to extracellular ATP.